2009
DOI: 10.1007/s10919-009-0079-9
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Stability Across Time and Situations: Nonverbal Versus Verbal Consistency

Abstract: Behavioral consistency has been at the center of debates regarding the stability of personality. We argue that people are consistent but that such consistency is best observed in nonverbal behavior. In Study 1, participants’ verbal and nonverbal behaviors were observed in a mock interview and then in an informal interaction. In Study 2, medical students’ verbal and nonverbal behaviors were observed during first- and third-year clinical skills evaluation. Nonverbal behavior exhibited consistency across context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…This may relate to inconsistencies often found between verbal and non-verbal behaviours in prison or special hospitals. The Weisbuch et al (2009) study supports the view of West and Greenall (2011), and an earlier observation by McDougall and Clark (1991), that verbal and physical behaviour of offenders were frequently contradictory. This is unsurprising given that interviews are still an important aspect of assessment for release.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…This may relate to inconsistencies often found between verbal and non-verbal behaviours in prison or special hospitals. The Weisbuch et al (2009) study supports the view of West and Greenall (2011), and an earlier observation by McDougall and Clark (1991), that verbal and physical behaviour of offenders were frequently contradictory. This is unsurprising given that interviews are still an important aspect of assessment for release.…”
supporting
confidence: 87%
“…In the study by Weisbuch et al (2009), the authors found that nonverbal behaviour exhibited consistency across context and time whereas verbal behaviour did not. Results from the current study support the notion of consistency of non-verbal behaviour across context and time.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many symbols and terms in chemistry make students attempted to memorize without understanding the meaning. In the theory of education and practice, the key of subject translation was to use the language, terms, and collection of vocabularies of the subject [21]. Verbal/nonverbal dimensions of chemistry related to the terms and languages in chemistry provides the most negative perception among the other dimensions.…”
Section: Students Perception Toward Chemistrymentioning
confidence: 99%
“…Given the important role of these genes in various social behaviors, we hypothesized that genetic polymorphisms in each of these genes would be associated with social integration. Because behaviors are relatively stable across time (Huesmann et al, 1984; Weisbuch et al, 2010), we used an average social integration score across repeated measures over time to reduce extraneous (i.e., non-genetic) variability in the phenotype and increase power to detect genetic determinants. In addition, we explore whether there is a sex-dependent mechanism impacting the association in the present study given the evidence of sex-dependent action of OXT and AVP (Carter, 1998; Gabor et al, 2012; Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%